Exploring the proper cultural content in Indonesian EFL textbooks viewed from intercultural perspectives - Muhammad Ona Irawan; Bukhari Daud (English Education Journal, 2021)
This research aimed to find out and to describe the cultural content of two Indonesian Senior High School EFL textbooks namely Buku Bahasa Inggris Kelas XII and Pathway to English 3 from the content of cultural information, the elements of surface and deep culture of Hall’s (1976) Iceberg theory and the dimension of intercultural communicative competence of Byram’s (1997). This study is a document analysis, and the writer used descriptive qualitative analysis. The data were collected by reviewing document and were analyzed based on the concept of Miles, Huberman, and Saldana (2014) which covered data condensation, data display, and drawing conclusion. The findings showed that the cultural information in both textbooks mostly presented by elements of surface culture. This research also showed that both textbooks had facilitated the three dimensions of intercultural communicative competence (knowledge, skill, and attitude), while the last dimension (critical cultural awareness) had not been achieved yet. In conclusion, the textbooks are still providing and facilitating the material in improving learners' language competency and cultural knowledge.